Investigations on effect of Eu3+ doping on structural, morphological and nonlinear optical features of chemically grown tin oxide nanostructures. (15th June 2021) - Vinod, Anjana; Ani, Aninamol; Antony, Albin; Anusha,; Poornesh, P; Perumal, Varadharaja; Hegde, Gopalkrishna; Kulkarni, Suresh D.
Abstract: We report the effect of europium doping on the structural, optical and nonlinear optical properties of SnO2 thin films. The undoped and europium doped films (Eu: SnO2 ) at various concentrations (1 wt%, 3 wt% and 5 wt%) were synthesized via low-cost spray pyrolysis technique. X-ray diffraction (XRD) studies confirmed tetragonal rutile structure of both undoped and Eu: SnO2 thin films. An additional XRD peak at 31.6° was observed for 5 wt% Eu: SnO2 thin films due to the formation of Eu2 O3 crystalline phase. The optical transmittance of Eu: SnO2 thin film has increased from 60% to 85% in visible region upon increasing europium concentration. The bandgap of Eu: SnO2 films was observed to be ~ 3.9 eV which further shows a nominal variation upon Eu doping. The PL spectroscopy studies shows emission peak along UV and red region corresponding to Near Band Edge (NBE) emission and oxygen vacancy defects incorporated in the films. The films exhibited good nonlinear optical properties upon europium doping indicating the applicability of grown films in future photonic devices.